2021
DOI: 10.3390/cancers13050977
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Long Non-Coding RNAs in Glucose Metabolism in Cancer

Abstract: The rapid and uncontrolled proliferation of cancer cells is supported by metabolic reprogramming. Altered glucose metabolism supports cancer growth and progression. Compared with normal cells, cancer cells show increased glucose uptake, aerobic glycolysis and lactate production. Byproducts of adjusted glucose metabolism provide additional benefits supporting hallmark capabilities of cancer cells. Long non-coding RNAs (lncRNAs) are a heterogeneous group of transcripts of more than 200 nucleotides in length. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 130 publications
0
18
0
Order By: Relevance
“…Through gene transcription and posttranscriptional modification, lncRNAs play a specific role in carcinogenesis and metastasis ( Du et al, 2020 ; Gao et al, 2020 ; Liu et al, 2021a ). Studies from Balihodzic have shown that the extraction of lncRNAs is related to glucose metabolism tumors ( Balihodzic et al, 2021 ). Chen noted that lncRNAs were associated with tumor autophagy in colorectal cancer ( Chen et al, 2021 ), and lncRNAs were also associated with tumor metabolism and tumor metastasis ( Xu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Through gene transcription and posttranscriptional modification, lncRNAs play a specific role in carcinogenesis and metastasis ( Du et al, 2020 ; Gao et al, 2020 ; Liu et al, 2021a ). Studies from Balihodzic have shown that the extraction of lncRNAs is related to glucose metabolism tumors ( Balihodzic et al, 2021 ). Chen noted that lncRNAs were associated with tumor autophagy in colorectal cancer ( Chen et al, 2021 ), and lncRNAs were also associated with tumor metabolism and tumor metastasis ( Xu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Long noncoding RNAs (lncRNAs) are the largest class of noncoding RNAs; these sequences are composed of more than 200 nucleotides and have rich biological functions. LncRNAs play crucial regulatory roles in modulating the cell cycle, cell proliferation, cell invasion, and migration by regulating gene expression at the transcriptional, post-transcriptional, and epigenetic levels ( 6 , 7 ). Studies have demonstrated that dysregulation of lncRNA expression is related to gliomas tumorigenesis and cancer progression and that it is a potentially effective early diagnostic, prognostic biomarker, and therapeutic target ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Ki-67 protein is a well-known tumor proliferation marker, with poor levels of Ki67 reflective of attenuated tumor growth [46]. Meanwhile, high glycolysis rates of cancer cells are an important factor for the rapid growth of tumor, and the glycolysis of tumor cells is related to the rapid proliferation of tumor cells [47,48]. Altogether, these findings and evidences suggested that silencing LINC00152 can inhibit tumor formation and glycolysis in pancreatic cancer cells through KLF7, and over-expression of KLF7 may promote the proliferation of PC cells in vivo by promoting the glycolysis of PC cells, and thus restore the growth of tumors.…”
Section: Discussionmentioning
confidence: 99%